1988
DOI: 10.1111/j.1528-1157.1988.tb04412.x
|View full text |Cite
|
Sign up to set email alerts
|

Phenytoin Levels in Catamenial Epilepsy

Abstract: We studied the fluctuations in phenytoin (PHT) levels during ovulatory and menstrual phases of the cycle, in eight patients with catamenial epilepsy and in eight age-matched controls. Pharmacokinetic studies of PHT were done in five patients with catamenial epilepsy. The difference in PHT levels during menstrual and ovulatory phase in catamenial group was 3.44 +/- 3.25 micrograms/ml as compared with 0.91 +/- 2.03 micrograms/ml in controls. The mean fall during menstrual phase was significant (p less than 0.05)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 20 publications
1
25
0
Order By: Relevance
“…Specifically, high levels of circulating oestrogen in the luteal phase could induce hepatic isoenzymes used for antiepileptic drug metabolism and thereby lower the levels of circulating antiepileptic drugs premenstrually, potentially permitting breakthrough seizures. 60 Rosciszewska and colleagues 61 reported that phenytoin levels on day 28 in women with catamenial seizures were significantly lower than those in women without cyclical exacerbations. Phenobarbital concentrations, however, did not change significantly.…”
Section: Endogenous Hormones and Catamenial Epilepsymentioning
confidence: 99%
“…Specifically, high levels of circulating oestrogen in the luteal phase could induce hepatic isoenzymes used for antiepileptic drug metabolism and thereby lower the levels of circulating antiepileptic drugs premenstrually, potentially permitting breakthrough seizures. 60 Rosciszewska and colleagues 61 reported that phenytoin levels on day 28 in women with catamenial seizures were significantly lower than those in women without cyclical exacerbations. Phenobarbital concentrations, however, did not change significantly.…”
Section: Endogenous Hormones and Catamenial Epilepsymentioning
confidence: 99%
“…Catamenial epilepsy, in many cases, is assumed to be an acquired disorder and currently there is no clear evidence of genetic components. A variety of mechanisms such as fluctuations in antiepileptic drug levels, changes in water and electrolyte balance, and physiological variation in ovarian hormone secretion have been proposed as causes for catamenial epilepsy (McQuarrie and Peeler, 1931; Ansell and Clarke, 1956; Shavit et al, 1984; Rosciszewska et al, 1986; Kumar et al, 1988; Narbone et al, 1990; Herzog, 1991; Herkes et al, 1993; Rodriguez-Macias, 1996; Harden et al, 1999; Tuveri et al, 2008). Overall, cyclical changes in the circulating levels of estrogens and progesterone are now widely accepted to play a central role in the development of this condition (Fig.…”
Section: Pathophysiology Of Catamenial Epilepsymentioning
confidence: 99%
“…20 Changing levels of estrogen and progesterone throughout the cycle may alter the metabolism of anticonvulsant drugs, via release of hepatic monooxygenase enzymes. 1,21 …”
Section: Examining Etiologic Factors In Menstrual Cycle Disease Exacementioning
confidence: 99%